CONCEPTS OF 'ULTRA-DIMENSIONS' AND 'THERMODYNAMICS' FOR YOUNG CELL BIOLOGISTS - Mishra, Arun K. (SCHOOL SCIENCE, 2013)
Cells are visible mostly through the help of optical microscope and their organelles usually are seen through the electron microscope. Various organelles of cells, though small in size, perform vital functions. All the food we consume is synthesised by tiny chloroplasts of the green plants and used up by still tinier mitochondria in the cell. The magnanimity of the tasks performed is inversely proportional to the size of the ‘performer.’ A young, high school cell biologist may know about the structures and functions of the various cell organelles, but he is hardly able to develop an appreciation of the diversity of the size-range on ultra-dimensional scale and the intricacies of the reactions on such minute sites. Further, the cellular processes, at least many of them, have been resolved in terms of chemical reactions which obey the same physico-chemical principles as applicable to in vitro systems. Therefore, a clear understanding of these principles becomes prerequisite of the teaching of the essentials of cell biology. In the present article an attempt has been made to show the way to teachers and students as to how to absorb and assimilate these ‘so called’ hard concepts.